Cytotoxic and antiproliferative activities of amphibian (anuran) skin extracts on human acute monocytic leukemia cells. (15th April 2020) - Spinelli, Roque; Barrero Guevara, Laura Andrea; López, Javier Alejandro; Camargo, Carolina Muñoz; Groot de Restrepo, Helena; Siano, Alvaro Sebastián
Abstract: The use of preparations derived from frog skins for curative purposes antedates research history and is perpetuated in current medicine. The skins of anuran's (frogs and toads) are a rich source of compounds with a great importance in the search of antibiotics, analgesics, immunomodulators, enzymatic inhibitors and antitumoral agents applying to human health. Nowadays, cancer is the second most common cause of mortality with more than 8.2 million of deaths worldwide per year. Acute monocytic leukemia is the subtype M5 of acute myeloid leukemia (AML) a cancer type with reduced survival rates in patients. The monocyte to macrophage differentiation plays an essential role increasing the expansion of AML cell lines. Herein we studied the cytotoxic and antiproliferative activities of eleven amphibian species of three families belonging to Argentinean zones, against THP-1 monocytes and THP-1 macrophages acute monocytic leukemia cell lines. The evaluated species showed pronounced deleterious effects on acute monocytic leukemia THP-1 cell lines, reducing cell proliferation and inducing apoptosis, autophagy and in some cases cell aggregation. Being this work of great importance for the study of new natural anti-cancer compounds. Graphical abstract: Image 1 Highlights: We report seven new amphibian species with antileukemia activity. The antiproliferative activity of skin extracts occurred via apoptosis and autophagy. Extracts aggregate tumoral cells and in some cases were non-toxic for healthy erythrocytes. Extracts induced leukemic macrophages death, preventing tumor progression.